INTEGRATING ZAKAH AND WAQF FOR DEVELOPING ISLAMIC ECONOMIC BOARDING SCHOOL (IEBS) PROJECT IN INDONESIA - Ahmad Rizal; Neneng Ela Fauziyah; Aminuddin Ma'ruf; Adib Susilo (Journal of Islamic Economics and Philanthropy, 2020)
As the most populous Muslim nation, Indonesia has a big potential to unlock its Islamic financial market. However, there is a call on human development in the field to ensure the sustainability of the system. This study attempts to investigate the untapped potential of youth generation in Indonesia. The paper employs a qualitative research in developing the waqf and zakah funds based on the practice of Forum Silaturrahim Studi Ekonomi Islam (FoSSEI). The study found that waqf and zakah funds in Indonesia might solve the Islamic financial literacy problem of the country. In addition, the paper suggested the framework on developing waqf and zakah funds in spreading the Islamic financial literacy through youth empowerment by designing Islamic Economic Boarding School (IEBS) project. The study recommended the policy makers to design robust zakah and waqf framework leading the industry and nation’s economy for the long-run prosperity.